The Influence of Instagram Social Media Marketing and Brand Image on Consumer Purchase Decisions at Delapan Enam Coffee - Deny Rolind Zabara; Nurrahmah Destrianingsih (Journal Of Marketing and Technology Management, 2025)
This study aims to analyze the influence of Instagram Social Media Marketing and Brand Image on consumers’ Purchase Decisions at Delapan Enam Coffee in Pringsewu Regency. The background of this research focuses on the decline in purchase decisions in 2024 as well as the suboptimal digital marketing efforts and brand image of the coffee shop. This research employs a quantitative method with an associative approach. A sample of 100 respondents was selected using a purposive sampling technique, with data collected through questionnaires and analyzed using validity tests, reliability tests, normality tests, linearity tests, multicollinearity tests, multiple linear regression, t-test, and F-test. The results indicate that Instagram Social Media Marketing has a significant influence on purchase decisions, and Brand Image also shows a significant effect. Simultaneously, both variables collectively influence purchase decisions. The coefficient of determination value of 0.120 indicates that the research variables explain 12% of the variation in purchase decisions, while the remaining 88% is influenced by other factors.